2018
DOI: 10.1002/smll.201870094
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Electronics: Defect‐Free, Highly Uniform Washable Transparent Electrodes Induced by Selective Light Irradiation (Small 21/2018)

Abstract: In article number https://doi.org/10.1002/smll.201800676, Kyoohee Woo, Jooho Moon, and co‐workers describe a simple, large area‐compatible, intense light‐induced patterning process to fabricate Ag nanoparticle–carbon nanotube‐based defect‐free, highly conductive, mesh transparent electrodes with exceptional durability after 100 washing test cycles, in which a variety of stress situations such as rubbing, folding, and crumpling occurs in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…AgNWs have advantages in the preparation of high-performance flexible transparent conductive electrodes [54][55][56]. Zhou et al reported a stretchable conductive film prepared by embedding AgNWs just below the surface of a porous thermoplastic polyurethane film by self-assembly process, the obtained film has a transmittance of 61% [57].…”
Section: Flexible Ep Electrodes Based On Conductive Polymersmentioning
confidence: 99%
“…AgNWs have advantages in the preparation of high-performance flexible transparent conductive electrodes [54][55][56]. Zhou et al reported a stretchable conductive film prepared by embedding AgNWs just below the surface of a porous thermoplastic polyurethane film by self-assembly process, the obtained film has a transmittance of 61% [57].…”
Section: Flexible Ep Electrodes Based On Conductive Polymersmentioning
confidence: 99%